The Role of Education in Preserving Javanese Ethical Values - Elly Kismini; Rini Iswari; Fajar Fajar (Komunitas, 2023)
The advancement of technology and information has influenced social and cultural changes within society. This phenomenon is also evident in Javanese society, known for its high cultural values. One of the Javanese cultural values undergoing shifts due to the influence of modernization and globalization, and thus requiring preservation, is Javanese ethical values. To preserve Javanese ethical values as part of the local culture, a collaborative educational process involving schools, families, and communities is necessary to shape individuals’ characters that reflect love for Indonesian culture. Education plays a crucial role in preserving the nation’s culture through the implementation of the noble values it encompasses. This research was conducted with a qualitative approach, focusing on junior high school students in North Semarang.